Implementasi Konsep “Now I See” pada Perancangan Interior Basecamp Komunitas Dance HOP Squad di Surabaya - Ria Gunawan; Ronald Hasudungan Irianto Sitindjak; Stephanie Melinda Frans (Intra, 2019)
Hip hop is no longer an unfamiliar word to hear in this modern era. Although there are already many facilities built for hip hop dancers in Indonesia, only few of them suit their needs. There is also a bad image associated with hip hop culture, specifically hip hop dancers. It is because they are known as rebel and low educated people. Based on the problems, interior design of HOP Squad community base camp will emphasize on those two aspects. They are the aspect of dancers urgency and the aspect of re-branding of hip hop image in society. This facility will provide facilities to rehearse, produce, and learn for dancers. It also can be a living gallery which can re-brand the hip hop image in society.